A method for monitoring junction temperature of IGBT module based on turn-off voltage - LAN Weiyin; CUI Wei; CHEN Wenxuan; ZOU Yingqiao; LI Jiacheng; GE Xinglai (机车电传动)
The precise junction temperature monitoring is of paramount importance for enhancing the reliability of insulated gate bipolar transistor (IGBT) modules and extending the lifespan of devices. This paper introduces a method for monitoring junction temperature of IGBT modules based on turn-off voltages (TOV), which highlights resistance to load currents. The study initially verified the rationality of using TOVs as a temperature-sensitive electrical parameter. The deep neural network (DNN) technology was subsequently employed to eradicate the dependence of TOVs on load currents, facilitating accurate junction temperature prediction under varying operational conditions. The proposed method was validated through a single-phase pulse width modulation (PWM) experiment. The findings reveal an error range of ±5 ℃ for this method, demonstrating the feasibility of optimizing junction temperature monitoring through DNN utilization.